Genetic landscape of ESBL producing international clone ST410 of Escherichia coli from pediatric infections in Shenzhen, China - Patil, Sandip; Pai, Liu; Chen, Hongyu; Chen, Yunsheng; Xinye, Li; Dong, Shaowei; Kaushik, Sanket; Lopes, Bruno Silvester; Chen, Xiaowen (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe emergence of ESBLs producing cephalosporin-resistant Escherichia coli isolates poses a threat to public health. This study aims to decipher the genetic landscape and gain insights into ESBL-producing E. coli strains belonging to the high-risk clone ST410 from pediatric patients.Methods29 E. coli ST410 isolates were collected from young children and subjected to antimicrobial susceptibility testing, Whole-genome sequencing (WGS), serotype analysis, MLST, ESBL genes, virulence genes, and plasmid profiling.ResultsAntimicrobial susceptibility testing demonstrated a high level of resistance to cephalosporins followed by aminoglycoside, sulfonamide, carbapenem and penicillin group of antibiotics. However, n=20/29 shows MDR phenotype. Phylogenetic group B2 (n=15) dominated, followed by group D (n=7), group A (n=4), and group B1 (n=3). Serotyping analysis identified O1:H7 (n=8), O2:H1 (n=6), O8:H4 (n=5), O16:H5 (n=4), and O25:H4 (n=3). Other serotypes identified included O6:H1, O15:H5, and O18:H7 (n=1 each). The most commonly detected ESBL genes were blaCTX-M, (n=26), followed by blaTEM (n=23), and blaSHV (n=18). Additionally, blaOXA-1 (n=10), blaOXA-48 (n=5), blaKPC-2 (n=3), blaKPC-3 (n=2), blaNDM-1 (n=4), blaNDM-5 (n=1), blaGES-1 (n=2), blaGES-5 (n=1), and blaCYM-1 (n=3). Notable virulence genes identified within the ST410 isolates included fimH (n=29), papC (n=24), hlyA (n=22), and cnf1 (n=18), among others. Diverse plasmids were observed including IncFIS, IncX4, IncFIA, IncCol, IncI2 and IncFIC with transmission frequency ranges from 1.3X10-2 to 2.7X10-3.ConclusionThe ST410 clone exhibited a complex resistance profile, diverse serotypes, the presence of specific resistance genes (ESBL genes), virulence gene repertoire, and diverse plasmids. The blaCTX-M was the most prevalent ESBL gene detected.